Determinants of tax avoidance in consumer non-cyclical companies: evidence from Indonesia - Amelia Maria Rosa d. L. M; Febriana Louw (Institute of Computer Science (IOCS), 2026)
This study examined the effect of managerial ownership, sales growth, capital intensity, and independent commissioners on tax avoidance in consumer non-cyclical companies listed on the Indonesia Stock Exchange during the 2021–2024 period. A quantitative approach was employed using secondary data obtained from annual financial reports. The sample consisted of 29 companies with 86 observations selected through purposive sampling. Data were analyzed using multiple linear regression. The results showed that managerial ownership had a negative and significant effect on tax avoidance, while sales growth had a positive and significant effect. In contrast, capital intensity and independent commissioners did not have a significant effect. The adjusted R-square value of 9.4% indicated that most of the variation in tax avoidance was explained by factors outside the model. These findings suggest that internal firm characteristics, particularly ownership structure and firm growth, play a more dominant role than governance mechanisms in influencing tax avoidance behavior. This study contributes by providing recent empirical evidence in the post-pandemic period and offers insights for improving corporate governance and tax compliance strategies.